Analysis of drying and dilution in phosphoric acid fuel cell (PAFC) using galvanometric study and electrochemical impedance spectroscopy - Paul, T. (2014)
Different experimental and analytical techniques namely steady state galvanometric study and electrochemical impedance spectroscopy (EIS) are employed to generate rule sets for identification of the acid drying and dilution phenomena in a phosphoric acid fuel cell (PAFC). The slope of steady state current versus voltage is used as a performance marker. A new parameter Î, which signifies the net moisture transport in PAFC, is introduced and evaluated from the experimental data to locate the regimes of electrolyte dilution and drying. Based on these two parameters, the performance of a PAFC is mapped on the plane of operating variables. Performance decay at higher cell temperature and lower humidifier temperature (below 60 Â°C) signifies acid drying; on the contrary the same at lower cell temperature and higher humidifier temperature is attributed to acid dilution. EIS is employed by imposing a sinusoidal potential excitation on steady state DC load and the shift of maximum phase angle position in the frequency spectrum is used as a diagnostic marker. Results show absence of peak in the domain of positive frequency for acid drying condition, while acid dilution causes the peak to be shifted at higher frequency value. Electrochemical timescales estimated from EIS increases by many order of magnitudes compared to that in a normal PAFC, when electrolyte drying occurs. The results obtained from EIS analysis are in agreement with the performance mapping based on galvanometric steady analysis. The results are significant in context of water management and humidity control in a PAFC. The tools and parameters introduced in the present publication show promising potential to map the performance and SOH of a PAFC on the plane of various operating variables. Results and logics revealed are of significance in development of inferential model for the online optimization of PAFC. Copyright Â© 2014 by ASME.